Daily ups and downs in adolescents' depressive symptoms: The role of daily self-criticism, dependency and basic psychological needs. (August 2021) - Vandenkerckhove, Beatrijs; Soenens, Bart; Flamant, Nele; Luyten, Patrick; Campbell, Rachel; Vansteenkiste, Maarten
Abstract: Introduction: Although associations between Blatt's personality dimensions of self-criticism and dependency and adolescents' depressive symptoms are well-established, only few studies have examined associations between these variables at the level of daily, within-person fluctuations. Moreover, our understanding of the mechanisms underlying this personality vulnerability to depressive symptoms is limited. Therefore, we studied (a) daily fluctuations in both personality and depressive symptoms over a 7-day period and (b) the possible interplay between daily variations in personality vulnerability, need-based experiences (as conceptualized in Self-Determination Theory), and depressive symptoms. This interplay was examined in terms of both a mediational and a moderating role of the need-based experiences. Methods: Participants were 121 Belgian adolescents ( M age  = 15.81; SD age  = 1.50; 52 % male) who completed questionnaires tapping into daily self-criticism, dependency, need-based experiences, and depressive symptoms every evening during seven consecutive days. Results & conclusions: Multilevel analysis revealed that self-criticism and dependency fluctuated substantially on a daily basis. These daily fluctuations in personality were related to daily fluctuations in depressive symptoms, with daily variation in need-based experiences mediating these associations. We found no evidence for interactions between personality and the need-based experiences. The findings underscore the importance of considering daily fluctuations in individuals' personality vulnerability and point to the explanatory role of need-based experiences in the relation between personality and depressive symptoms on a daily basis.